Estrategias didácticas para el desarrollo del lenguaje en los niños de 5 años de la Unidad Educativa Guayaquil del cantón Vinces - Moran Molina, Denia Lucia (2022)
Teaching strategies are a set of actions that teachers perform, in a planned manner, to achieve specific learning objectives. Didactic strategies is one of those methodologies since they are techniques that can be applied in laborious teachings, as is the case of language development. The main objective of language development is to help develop and enhance speech and language, through techniques, methods, skills and teaching resources. Therefore, the main purpose of this research is to analyze how didactic strategies promote the development of the language of 5-year-old children from the ´´Guayaquil´´ Educational Unit of the Vinces canton. The research used in this research project is documentary - explanatory - bibliographic because its primary objective is to systematically analyze and explain. This analysis has a contribution from different authors who, through web books and pages or electronic sites, favor to dignify this research.